Treatment of Relapsed Chronic Subdural Hematoma in Four Young Children with Atorvastatin and Low‐dose Dexamethasone. Issue 7 (28th May 2019) - Huang, Jinhao; Li, Lihong; Zhang, Jingyi; Gao, Chuang; Quan, Wei; Tian, Ye; Sun, Jian; Tian, Qilong; Wang, Dong; Dong, Jingfei; Zhang, Jianning; Jiang, Rongcai
Abstract : Chronic subdural hematoma (CSDH) can develop in children in rare cases. Burr‐hole drainage (BHD) is the treatment of choice, but it is associated with a high rate of recurrence. This report describes four cases of pediatric patients (1–7 yrs of age) with post‐BHD relapsed CSDH who were successfully treated with a drug regimen that included 2.5–5 mg atorvastatin daily combined with dexamethasone with stepwise‐decreasing dosing for a total of 4 weeks. After 4 weeks of treatment, the hematoma was completely resolved in three patients and significantly reduced in one patient. During the treatment, no patient reported clinically significant adverse events. No patient experienced hematoma relapse during the follow‐up period that lasted for up to 4 years. This case report suggests the need for a randomized placebo‐controlled trial to evaluate this drug regimen for nonsurgical treatment of patients with relapsed CSDH.